501 reading comprehensión questions. (Learning Express, 2010)
This book is best used to build your critical reading and thinking skills, but you might want to support it with some other LearningExpress Skill Builders Practice books.When it comes to perfecting your reading comprehension,donÕt ignore any of the other language skills.You will find Writing Skills Success in 20 Minutes a Day, Vocabulary and Spelling Success in 20 Minutes a Day, 501 Logic and Reasoning Problems, and 1001 Vocabulary and Spelling Questions to be indispensable guides. In any case, the more you use the language and understand the building blocks, the easier and faster you will breeze through those reading comprehension passages that you find on most tests.